PRODUCTIVITY, ECONOMIC AND ENERGY EFFICIENCY OF SHORT CROP ROTATION UNDER DIFFERENT SYSTEMS OF BASIC TILLAGE AND FERTILIZATION IN THE RIGHT BANK FOREST STEPPE OF UKRAINE - Ivan PRYMAK; Yriy FEDORUK; Mykola GRABOVSKYI; Mykola LOZINSKYI; Tatiana LOZINSKA; Nataliia PRYSIAZHNIUK; Igor POKOTYLO; Nataliia FEDORUK; Inna PANCHEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The efficiency of four systems of basic soil tillage and four systems of crop fertilization of five-field crop rotation was studied. Areas of cultivation options were systematically placed in one tier, and fertilizers – in four tiers in a row. Plowing was carried out with a plow, tillage with a deep cultivator, and shallow plowing with a heavy disc harrow. The highest yields of soybeans, winter wheat and corn were under mouldboard, and sunflower and spring barley – under mouldboardless tillage in crop rotation. Under systematic mouldboardless and disk tillage in crop rotation, the yield of all crops decreased significantly, and with increasing fertilizer rates, the difference between these cultivation options and control increased. Crop rotation productivity was almost at the same level under mouldboard and mouldboardless tillage; under the other studied options it was significantly lower. In terms of economic and energy efficiency, under differentiated cultivation the advantage was with the application of 12 tons of manure per hectare of arable land + N95P82K72. In terms of crop rotation productivity, mouldboard and differentiated tillage were equivalent, and in terms of economic and energy efficiency, the latter exceeded control. For all four variants of tillage in crop rotation, the highest energy efficiency coefficient was recorded for the annual application of 12 tons of manure per hectare of arable land + N95P82K72.